SEDIMENTOLOGIC AND VOLCANOLOGIC INVESTIGATION OF THE DEEP TYRRHENIAN SEA: PRELIMINARY RESULTS OF CRUISE VST02 - Gamberi F.; Marani M.; Landuzzi V.; Magagnoli A.; Penitenti D.; Rosi M.; Bertagnini A.; Di Roberto A. (My University, 2006)
The VST02 cruise carried out in the summer of 2002 focused on sedimentologic and volcanologic research over selected areas of the deep portion of the Tyrrhenian Sea. Chirp lines and seafloor samples were collected from the Calabrian slope surrounding Stromboli Island, in the Marsili deep-sea fan, in the Vavilov Basin and in the Vavilov seamount. Submarine volcanic activity, both explosive and effusive, is occurring in the Stromboli edifice. Explosive submarine volcanism also affects the shallowest areas of the Vavilov seamount. Submarine carbonate lithification has been observed on the sediment-starved flanks of the Vavilov seamount. Acoustic transparent layers make up the recentmost infill of the Gortani Basin, the easternmost portion of the Vavilov Basin. Channels comprised of a variety of architectural elements and depositional lobes are the main elements of the Marsili deep-sea fan where, apparently, sedimentation occurs mainly through debris flow processes.
Keywords: ACOUSTIC TRANSPARENT LAYERS; CARBONATE CRUSTS; DEEP-SEA FAN; SUBMARINE VOLCANIC EXPLOSIONS; SUBMARINE VOLCANISM